Glioblastoma‐mesenchymal stem cell communication modulates expression patterns of kinin receptors: Possible involvement of bradykinin in information flow. (15th December 2015) - Pillat, Micheli M.; Oliveira, Mona N.; Motaln, Helena; Breznik, Barbara; Glaser, Talita; Lah, Tamara T.; Ulrich, Henning
Abstract: The most aggressive subtype of brain tumors is glioma WHO grade IV, the glioblastoma (GBM). The present work aims to elucidate the role of kinin receptors in interactions between GBM cells and mesenchymal stem cells (MSC). The GBM cell line U87‐MG was stably transfected to express dsRed protein, single cell cloned, expanded, and cultured with MSC, both in the direct co‐cultures (DC) and indirect co‐cultures (IC) at equal cell number ratio for 72 h. Up‐ and down‐regulation of matrix metalloproteases (MMP)−9 expression in U87‐MG and MSC cells, respectively, in direct co‐culture points to possible MSC participation in tumor invasion. MMP9 expression is in line with significantly increased expression of kinin B1 (B1R) and B2 receptor (B2R) in U87‐MG cells and their decreased levels in MSC, as confirmed by quantitative assessment using flow cytometric analysis. Similarly, in indirect cultures (IC), lacking the contact between GBM and MSC cells, an increase of B1 and B2 receptor expression was again noted in U87‐MG cells, and no significant changes in kinin receptors in MSC was observed. Functionality of kinin‐B1 and B2 receptors was evidenced by stimulation of intracellular calcium fluxes by their respective agonists, des‐Arg9‐bradykinin (DBK) and bradykinin (BK). Moreover, BK showed a feedback control on kinin receptor expression in mono‐cultures, direct and indirect co‐cultures. The treatment with BK resulted in down‐regulation of B1 and B2 receptors in MSC, with simultaneous up‐regulation of these receptors in U87‐MG cells, suggesting that functions of BK in information flow between these cells is important for tumor progression and invasion. © 2015 International Society for Advancement of Cytometry